Sponsorship bias and quality of randomised controlled trials in veterinary medicine - Wareham, Kathryn; Hyde, Robert; Grindlay, Douglas J.C.; Brennan, Marnie L.; Dean, Rachel S. (BioMed Central, 2017)
Background: Randomised controlled trials (RCTs) are considered the gold standard form of evidence for assessing treatment efficacy, but many factors can influence their reliability including methodological quality, reporting quality and funding source. The aim of this study was to examine the relationship between funding source and positive outcome reporting in veterinary RCTs published in 2011 and to assess the risk of bias in the RCTs identified. Methods: A structured search of PubMed was used to identify feline, canine, equine, bovine and ovine clinical trials examining the efficacy of pharmaceutical interventions published in 2011. Funding source and outcomes were extracted from each RCT and an assessment of risk of bias made using the Cochrane risk of bias tool. Results: Literature searches returned 972 papers, with 86 papers (comprising 126 individual RCTs) included in the analysis. There was found to be a significantly higher proportion of positive outcomes reported in the pharmaceutical funding group (P) compared to the non-pharmaceutical (NP) and ‘no funding source stated’ (NF) groups (P = 56.9%, NP = 34.9%, NF = 29.1%, p < 0.05). A high proportion of trials had an unclear risk of bias across the five criteria examined. Conclusions: We found evidence that veterinary RCTs were more likely to report positive outcomes if they have pharmaceutical industry funding or involvement. Consistently poor reporting of trials, including non-identification of funding source, was found which hinders the use of the available evidence.